2022
DOI: 10.1094/php-05-22-0047-dg
|View full text |Cite
|
Sign up to set email alerts
|

Rose Rosette Disease: A Diagnostic Guide

Abstract: Rose Rosette Disease (RRD) is a common disease of roses, predominantly in North America. RRD is caused by the rose rosette virus (RRV), an emaravirus transmitted by the eriophyid mite Phyllocoptes fructiphilus Keifer. The RRD characteristic symptoms include deformed leaves, abnormal thorns, and witches’ brooms. Roses are important cultivated plants around the world. Most Rosa spp. and cultivated varieties such as climbers, hybrid teas, floribundas, and miniature roses are susceptible to the disease. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…RRV symptoms in roses vary according to the cultivar, plant developmental stage, and between shooting branches of a bush [28][29][30]. Endpoint PCR and RT-qPCR are preferred for diagnostic detection of RRV infection in roses [7,25,28,31,32], although a few studies reported false negative results [5,13]. Given recent advances in the RT-PCR technology detecting RRV in infected rose leaves, we selected the most reliable RT-PCR primers to re-examine the host range of RRV.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…RRV symptoms in roses vary according to the cultivar, plant developmental stage, and between shooting branches of a bush [28][29][30]. Endpoint PCR and RT-qPCR are preferred for diagnostic detection of RRV infection in roses [7,25,28,31,32], although a few studies reported false negative results [5,13]. Given recent advances in the RT-PCR technology detecting RRV in infected rose leaves, we selected the most reliable RT-PCR primers to re-examine the host range of RRV.…”
Section: Discussionmentioning
confidence: 99%
“…Until the past decade, most reports using Koch's postulates to investigate RRV transmission to indicator plants have been assessed for visual evidence of disease with few attempts to use molecular diagnostic detection [7,19,26,27]. We employed the most recently developed and widely used diagnostic RT-PCR methods to amplify RRV sequences and to study virus accumulation in mechanically inoculated plants [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations